Obese non-Hodgkin lymphoma patients tolerate full uncapped doses of chemotherapy with no increase in toxicity, and a similar survival to that seen in nonobese patients. Issue 11 (1st November 2016) - Chan, Henry; Jackson, Sharon; McLay, Jessica; Knox, Angela; Lee, Jae; Wang, Sarah; Issa, Samar
Abstract: The aim of this study is to compare the risk of treatment-related toxicities and long-term survival between obese and nonobese patients with non-Hodgkin lymphoma when treated with full uncapped doses of R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) chemotherapy. A total of 133 patients and 733 cycles of chemotherapy were analyzed. Obese patients did not experience an increased risk of acute treatment-related toxicities (adjusted odds ratio 0.825, p = 0.197), or delayed toxicities (adjusted odds ratio 0.819, p = 0.779). In the subgroup of diffuse large B-cell lymphoma patients ( n = 109), treatment response rate was similar between the two body mass index (BMI) groups, and obese patients tended to have superior overall and progression-free survivals, albeit not statistically significant. Full uncapped doses of R-CHOP chemotherapy administered to obese patients with non-Hodgkin lymphoma (NHL) are safe, well tolerated, and do not lead to inferior treatment response or long-term outcomes.